Poly (trimethylene carbonate)/doxycycline hydrochloride films in the treatment of Achilles tendon defect in rats - Zhang, Jinchi; Zhang, Xiaowei; Li, Wei; Guo, Jing; Yang, Liqun; Yan, Guangqi (Frontiers in Bioengineering and Biotechnology, 2023)
In this study, Poly (trimethylene carbonate)/Doxycycline hydrochloride (PTMC/DH) films were introduced to repair the Achilles tendon defects for the first time. (PTMC/DH) films with different DH content of 10, 20, and 30% (w/w) were prepared by solvent casting. The in vitro and in vivo drug release of the prepared PTMC/DH films was investigated. The results of drug release experiments showed that the PTMC/DH films released effective concentrations of doxycycline for more than 7 and 28 days in vitro and in vivo, respectively. The results of antibacterial activity experiments showed diameters of 25.00±1.00 mm, 29.33±1.15 mm, and 34.67±1.53 mm, respectively, for the inhibition zones produced by the release solutions of PTMC/DH films with 10, 20 and 30% (w/w) DH at 2 hours, indicating that the drug-loaded films could inhibit Staphylococcus aureus well. After treatment, the Achilles tendon defects have recovered well, as indicated by the more robust biomechanical properties and the lower fibroblast density of the repaired Achilles tendons. Pathology revealed that the pro-inflammatory cytokine, IL-1β, and the anti-inflammatory factor, TGF-β1, peaked in the first three days and gradually decreased as the drug was released more slowly. These results demonstrated that the PTMC/DH films have great potential for regenerating Achilles tendon defects.